Desenvolvimento e estudos de tintas epóxis anticorrosivas ecologicamente corretas - Leite, Adriana de Oliveira Sousa (2004)
This work describes the development and study of environmental friendly epoxies anticorrosives paints, which were formulated using zinc phosphate (ZP), zinc molybdate (ZM), zinc and calcium molybdate (ZCM), zinc phosphomolybdate (ZMP) and zinc and calcium phosphomolybdate (MZAP), as safe alternative to more traditional anticorrosive pigments (lead, chromium and other heavy metals). Additionally, environmental considerations are limiting the use of solvent-borne paints because it contibutes to atmospheric pollution and empairs health problems. Thus, hydrosoluble epoxy resin was used in the formulation of the water-borne paints. The aim od this research is to employ molybdate-based pigments in order to check their efficiency in water borne paints. Inhibitive properties of the pigments were evaluated by potentiodynamic polarization curves, open ciricuit potential (Eoc) and mass loss monitoring during 30 days in immersion test of SAE 1010 steel in aqueous saturated pigment solutions with 10-2 mol dm-3 NaCl. The physical chemical characterization of the corrosion products was carried out by scanning electron microscopy, energy dispersive X-ray and X-ray diffraction techniques. All the tests showed that the phosphomolybdate pigments presented the better corrosion inhibiting properties. All the paints were formulated with 16% (v/v) epoxy resin, 7.5 % (v/v) anticorrosive pigment, and additives and fillers in order to maintain the PVC/CPVC ration equal to 0.8. the dry thickness of the painted samples was approximately 120 μm. The paint performance was monitored by electrochemical impedance spectroscopy (EIS) during immersion tests, of the atmospheric exposition and accelerated ensay of salt spray. The thermal stability of the paintings was also studied by thermal gravimetry and differential scanning calorimetry. The impedance diagrams of all painted samples showed only one capacitive loop, with impedance values higher than 109 Ωcm2. Capacitance values varied between 10-6 and 10-10 Fcm-2. The results suggest that the combination of the molybdate and phosphate gives the best inhibitive properties. About the thermal analyses were observed that the molybdates and phosphomolybdates pigments showed the better performances thus in the thermal stability of epoxy resin, because theses pigments showed higher interaction between pigment-resin; just as in the relation the energy involved in the cure process of polymeric film, because these pigments contribued to reduce the heat involved in the cure process